PENGEMBANGAN MULTIMEDIA INTERAKTIF EDUBENA (EDUKASI BENCANA ALAM) UNTUK SISWA KELAS VII - Irwanda, Yulia; Hidayati, Abna; Pratiwi, Rahmi; Masnur, Alkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the need to improve students' understanding of natural disaster concepts due to the high level of disaster risk in West Sumatra. Social Studies learning in Grade VII at SMP Negeri 39 Padang still relied on textbooks, student worksheets, and simple PowerPoint presentations, which had not optimally supported the learning process. This study employed a Research and Development (R&D) approach using the ADDIE model to develop EduBena interactive multimedia that is valid, practical, and effective. The research subjects consisted of expert validators, one Social Studies teacher, and 30 Grade VII students of SMP Negeri 39 Padang. Data were collected through validation sheets, practicality questionnaires, learning implementation observation sheets, and learning achievement tests, and were analyzed using descriptive quantitative analysis and the N-Gain test. The results showed that EduBena achieved validity scores of 99.33% from the media expert and 94.66% from the material expert, both categorized as highly valid. The practicality scores reached 91.96% based on students' responses and 96% based on the teacher's response, both categorized as highly practical. The multimedia was also effective in improving students' average learning outcomes from 76.53 to 96.53. Therefore, EduBena interactive multimedia is considered valid, practical, and effective, making it suitable for use in teaching natural disaster topics.